Perilaku Masyarakat dalam Pengendalian Kasus Malaria dengan Menggunakan Kelambu Berinsektisida - Dhorkas Marpaung; Andreas Ayomi (Journal of Pharmaceutical and Health Research, 2022)
The use of insecticide-treated nets is an effort to reduce the incidence of malaria in the community. The Ministry of Health routinely distributes mosquito nets through the mass netting program to people in malaria-endemic areas. Mimika Regency is a district with high endemicity, with an API of 289.06 per 1000 population. The purpose of this study is to determine the relationship between people's knowledge, attitudes, and behavior in Timika City when it comes to preventing malaria by using insecticide-treated mosquito nets.This research was conducted using a cross-sectional study design from June through August 2022 in Timika City, Mimika Regency. The number of sample respondents planned for this study amounted to 73 respondents spread across 9 districts in Timika City. The sample selection was carried out by incidental sampling. The data were described univariately and bivariately with chi-square analysis.The 104 respondents who obtained the most were in Kamoro Jaya (21.2%); the largest age group was aged 31–40 years (34.6%); and 52.9% of respondents did not work. Respondents who had good knowledge of the use of mosquito nets were 38 (36.5%); those with positive attitudes towards the use of mosquito nets were 40 (38.4%); and those with good behavior towards the use of mosquito nets were 34 (32.6%). From the results of the chi-square test, knowledge, attitudes, and behavior have not significantly reduced the incidence of malaria in Timika City.The incidence of malaria in an area cannot only be reduced by increasing the knowledge, attitudes, and behavior of the community toward using mosquito nets. However, there are other risk factors that play a role; therefore, further research is needed to determine the most dominant risk factor that can reduce the incidence of malaria.